Pengaruh Gaya Mengajar Resiprokal Terhadap Hasil Belajar Passing Atas Bola Voli Siswa SMK - Agustinus Himan; Yuliana Sattu; Eduard E. Kumenap (STIKES Columbia Asia Medan, 2025)
This study aims to determine the effect of applying the reciprocal teaching style on students’ learning outcomes in the basic overhead passing technique in volleyball at SMK Negeri 1 Tombulu. The research was motivated by the students’ low ability to perform effective overhead passing in physical education lessons. An experimental method with a randomized control group pre-test and post-test design was used. The sample consisted of two groups: an experimental group taught using the reciprocal style and a control group that received no treatment. Data were collected through a skill test and analyzed using the t-test. The results revealed a significant improvement in the experimental group compared to the control group. This finding indicates that the reciprocal teaching style is effective in enhancing students’ mastery of basic volleyball skills. The study highlights important implications for physical education teachers in selecting effective teaching methods to improve students' motor skills.